Investıgatıon of genetıc dıversıty, phylogenetıc and chemotaxonomıc relatıonshıps ın some opıum poppy (papaver somniferum l.) cultıvars ın Turkey - Şen, Uğur (My University, 2017)
Papaveraceae familyası dünya üzerinde 28 cins ve yaklaşık 250 tür içermektedir. Bufamilyanın üyeleri, kuzey yarımkürede subtropikal bölgelerde yayılım göstermektedir.

Papaveraceae family includes 28 genera and approximately 250 species around the world.Members of this family are spread on subtropical regions in Northern Hemisphere.
Keywords: Farmasötik özellikleri; filogeni; GC-FID; Haşhaş; Haşhaş türleri; ICP-MS; ISSR; ITS; Papaver L.-- Türkiye; phylogeny; trnL- trnF; trnL- trnF Opium poppy; Türkiye